Enhancing Early Childhood Art Development through Music and Dance Education - Khai Rani; Hilda Zahra Lubis; Sindi Pratiwi; Emilia Fitri Harahap (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
Learning the art of music is no longer strange when you are at RA/TK because music serves as a foundation for learning from start to finish. Learning the art of music is very important for young children because music plays a significant role in fostering and improving memory. This happens because when children listen to music, their brain cells work more actively, making children more enthusiastic about learning, especially when they play music or a musical instrument. This activity helps train motor skills and develop sensitivity to coordinate various senses. Meanwhile, learning the art of music using musical instruments at RA Al-Kamal is rarely implemented. It is only during certain events that children are taught to play several musical instruments at RA Al-Kamal.